2022
DOI: 10.3389/fpls.2022.1020367
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of transcriptome and metabolome reveals the molecular mechanism and candidate genes of Haloxylon drought tolerance

Abstract: Haloxylon ammodendron and Haloxylon persicum, as typical desert plants, show strong drought tolerance and environmental adaptability. They are ideal model plants for studying the molecular mechanisms of drought tolerance. Transcriptomic and metabolomic analyses were performed to reveal the response mechanisms of H. ammodendron and H. persicum to a drought environment at the levels of transcription and physiological metabolism. The results showed that the morphological structures of H. ammodendron and H. per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 102 publications
1
3
0
Order By: Relevance
“…Thus, it was found that ‘Jilv3’ under drought stress sufficiently maintained its energy supply by regulating the TCA cycle. This result is consistent with previous reports of enhanced TCA cycle under drought stress in wheat [ 21 ] and Haloxylon [ 22 ]. Citrate is essential in drought stress [ 48 ].…”
Section: Discussionsupporting
confidence: 94%
“…Thus, it was found that ‘Jilv3’ under drought stress sufficiently maintained its energy supply by regulating the TCA cycle. This result is consistent with previous reports of enhanced TCA cycle under drought stress in wheat [ 21 ] and Haloxylon [ 22 ]. Citrate is essential in drought stress [ 48 ].…”
Section: Discussionsupporting
confidence: 94%
“…Figure 5A shows that most members of the six TF families (bHLH, HSF, MYB, ARR, WRKY and C2H2) were upregulated under drought stress treatment, indicating their potential role in positive regulation. The positive regulatory roles of HSF, WRKY, MYB, bHLH, ARR and C2H2 in the plant response to drought stress have been demonstrated in previous studies ( Kang et al., 2013b ; Yang and Lv, 2022 ). Additionally, most members of the GRF, TCP and B3 TF families were upregulated, and these TFs are known to regulate various growth and developmental processes, such as leaf development, flower symmetry and bud branching ( Liu et al., 2014 ; Parapunova et al., 2014 ; Zhang et al., 2014 ).…”
Section: Discussionsupporting
confidence: 68%
“…Studies conducted in Arabidopsis thaliana, for example, have shown significant accumulation of dihydroflavonols and anthocyanins under drought stress (Nakabayashi et al, 2014;Zandalinas et al, 2016). Yang and Lv (2022) found that vitexin and naringenin were significantly increased in Haloxylon amsenjimodendron under drought stress. In our study, dihydroquercetin and quercetin significantly accumulated (Figure 9A) under drought stress treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5A shows that most members of the six TF families (bHLH, HSF, MYB, ARR, WRKY and C2H2) were upregulated under drought stress treatment, indicating their potential role in positive regulation. The positive regulatory roles of HSF, WRKY, MYB, bHLH, ARR and C2H2 in the plant response to drought stress have been demonstrated in previous studies (Kang et al, 2013b;Yang and Lv, 2022). Additionally, most members of the GRF, TCP and B3 TF families were upregulated, and these TFs are known to regulate various growth and developmental processes, such as leaf development, flower symmetry and bud branching Parapunova et al, 2014;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 62%